2020
DOI: 10.3390/pharmaceutics12010079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Cell Lines and Three-Dimensional Mucociliary Tissue Model Systems to Estimate Drug Permeability Using an In Vitro Transport Study to Predict Nasal Drug Absorption in Rats

Abstract: Recently, various types of cultured cells have been used to research the mechanisms of transport and metabolism of drugs. Although many studies using cultured cell systems have been published, a comparison of different cultured cell systems has never been reported. In this study, Caco-2, Calu-3, Madin–Darby canine kidney (MDCK), EpiAirway and MucilAir were used as popular in vitro cell culture systems, and the permeability of model compounds across these cell systems was evaluated to compare barrier characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…Despite the changes in cell cohesion values, TEER values always exceeded 300 Ω*cm 2 during the exposure time. These values agree with others studies where researchers reported TEER values around 600 Ω*cm 2 [56,58], or lower [59,60].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the changes in cell cohesion values, TEER values always exceeded 300 Ω*cm 2 during the exposure time. These values agree with others studies where researchers reported TEER values around 600 Ω*cm 2 [56,58], or lower [59,60].…”
Section: Discussionsupporting
confidence: 93%
“…Manufacturers STEMCELL Technologies and Epithelix provide an own proliferation medium to combine with Pneu and Epi. The choice of alternative proliferation media in the initial expansion phase in the inserts could also explain the successful use of Pneu and Epi in earlier studies reported in the literature 13,27,28 . Unfortunately, not all studies list the proliferation medium used.…”
Section: Discussionmentioning
confidence: 96%
“…The endocytosis of fluorescently labelled random methyl-beta-cyclodextrin, (2-hydroxypropyl)-beta-cyclodextrin and soluble beta-cyclodextrin polymer cross-linked with epichlorohydrin has been already revealed [32,33]. CACO-2 cells were chosen because they grow in culture as an adherent monolayer of epithelial cells compared to PC12 and they are suitable for transport studies [34]. The uptake evaluated by confocal microscopy showed that after 30 min, all monomeric and polymeric fluorescent beta-cyclodextrins were internalized in the cytoplasm of CACO-2 cells with different efficiency.…”
Section: Discussionmentioning
confidence: 99%